Effect of Oxygen Flow Rate on Combustion Time and Temperature of Underground Coal Gasification - Apriansyah Zulatama; Aida Syarif; Muhammad Yerizam (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
Underground Coal Gasification (UCG) is a process of converting coal in the ground into synthetic gas that has economic value. In the UCG process which will be carried out in the UCG prototype assisted by the presence of oxygen as a gasification agent, which this gasification agent will help the process of burning coal in the ground. The flow rate of oxygen in the process of UCG affecting the coal combustion temperature and effective flame from burning coal. The highest temperature at a flow rate of 5 l/min is 240oC, at an oxygen flow rate of 3 l/min the highest temperature is 143oC and at an oxygen flow rate of 2 l/min the highest temperature is 135oC and time effective flame at a flow rate of 5 l / min ie 80 minutes, effective burning time on the speed of the flow rate of 3 l / min ie for 120 minutes and time effective flame at a flow rate of 2 l / min ie for 165 minutes. This study proves that the greater the oxygen flow rate is used as the gasification agent at UCG process the lignite coal combustion temperatures will be high and effective flame coal combustion process will be more brief.